Efisiensi ICU Rumah Sakit Pemerintah Dengan Metode Data Envelopment Analysis (DEA) - Salsabila, Hilwa; Saputra, Irwan; Syahrizal, Dedy; Zaman, Nasrul; Usman, Said (STIKES Yayasan RS.Dr.Soetomo, 2024)
Efficiency defined by optimizing any resources which used to produce an output in a maximal level. Since INA-CBG was applied to hospital payment system, hospital was forced to keep the resources that used for producing process is less than the cost of National Health Assurance. Intensive Care Unit (ICU) is a ward needed advanced technology. qualified human resources, and high cost. Thus, ICU should be concern about their efficiency. Aim of this study is to measure the efficiency of the ICU at a public hospital. This is a quantitative study with a cross-sectional design. The study was conduct at type A public hospital in Banda Aceh, Aceh Province, Indonesia. We include six units of intensive care such as MICU, CSICU, ICCU, PICU, NICU, RICU. Data Envelopment Analysis (DEA) model is used to measure the efficiency at period 2022. DEA measurement performed by MAXDEA Lite 2.0. Results: ICU, CSICU, ICCU, PICU, and RICU efficiency score was one (efficient), while NICU was 0,87 (inefficient). Conclusion of the study that MICU, CSICU, ICCU, PICU, and RICU are efficient. NICU are not efficient.